Youth employment problems - Bilokon, S. A. (ТДАТУ, 2019)
These options will allow students to be at the enterprise during the educational process and see clearly what knowledge they need, as well as receive relevant information in the learning process. The most important thing is to gain practical experience and modern knowledge for further professional activities and receive initial employment assistance to gain valuable experience.
Keywords: the employment; young professionals; employers